Pengembangan Sumber Daya Manusia Berbasis Kewirausahaan bagi Pelajar di Yayasan Tajaul Karomatu Kabupaten Tangerang - Darmadi Darmadi; Endang Sugiarti; Noto Susanto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This community service program (PKM) was conducted to strengthen entrepreneurial-based human resource development among students at Yayasan Tajaul Karomatu, Kabupaten Tangerang. The background of this activity stems from the need to cultivate an entrepreneurial mindset and essential skills in young learners to prepare them for future economic challenges and opportunities. The program aimed to enhance students’ knowledge, creativity, and confidence in entrepreneurship through structured learning and hands-on experience. The PKM was implemented on 7–8 October 2025 by six lecturers from Universitas Pamulang and involved 40 ninth-grade students. The implementation methods included material presentation, practical activities, group discussions, and question-and-answer sessions. The activity followed three main stages: preparation, execution, and reporting. The results indicated an increase in students’ understanding of basic entrepreneurial concepts, improved ability to generate simple business ideas, and greater enthusiasm for exploring entrepreneurship as a potential future pathway. Students also demonstrated stronger soft skills, such as teamwork and communication, during the practice and discussion sessions. Overall, the PKM program effectively fostered entrepreneurial awareness and skills among participating students, contributing to the development of more innovative and adaptable young human resources.